Spherical hard carbon/graphite anode for high performance lithium ion batteries. - Xingqun Liao; Dalin Hu; Lijuan Yu; Bin Li; Feng Xiao; Shanxing Wang (PLoS ONE)
The issue of long charging time for electric vehicles has been a matter of serious concern, and the problem is mainly stemmed from the graphite anode. The slow kinetics of pure graphite can lead to the formation of the lithium metal during fast charging, which triggers cycle degradation and safety issues of electric vehicles. In order to ameliorate the fast charging issue, a spherical hard carbon/graphite porous electrode is devised. Based on this, the discharge capacity ratio at 3C shows an improvement of about 40% at 25°C and at 1C shows an improvement of about 18% at 0°C. Additionally, the 300-cycle capacity retentions exhibit increases of 12% and 14% at temperature of 25°C and 50°C, respectively. Generally, the analysis shows that the spherical hard carbon/graphite porous electrode has more uniform porous structure, shorter transport path, less nano-scale powder and a certain voltage buffer ability compared to the pure graphite powder system, which enhance the ion transport kinetics, and reduce the side reactions under the high temperature, so as to effectively improve the fast charging performance and cycle life of the LIBs. It is also proved that the kinetics improvement is not only attributed to the high kinetics inherited from the instinct of hard carbon, but also the porous electrode structures constructed by the two-size powder system of graphite and hard carbon.